Effect of foods and drinks on primary tooth enamel after erosive challenge with hydrochloric acid - Késsia Suênia Fidelis de MESQUITA-GUIMARÃES; Camila SCATENA; Maria Cristina BORSATTO; Antonio Luiz RODRIGUES-JÚNIOR; Mônica Campos SERRA (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The aim of this study was to evaluate the effect of industrialised foods and drinks on primary tooth enamel previously eroded with hydrochloric acid (HCl). The crowns of one hundred two specimens were subjected to an erosive challenge with HCl and randomly divided into six groups (n = 17): Chocolate Milk (Toddynho® - Pepsico) - negative control; Petit Suisse Yogurt (Danoninho® - Danone); Strawberry Yogurt (Vigor); Apple puree (Nestlé); Fermented Milk (Yakult® - Yakult); and Home Squeezed Style Orange Juice (del Valle) - positive control. The 28-day immersion cycles for the test products were performed twice daily and were interspersed with exposure of the test substrate to artificial saliva. Measurements of enamel surface microhardness (SMH) were performed initially, after immersion in HCl and at 7, 14, 21 and 28 days of experimentation. A two-way ANOVA, according to a split-plot design, followed by the sum of squares decomposition and Tukey's test, revealed a significant effect for the interaction between Foods and Drinks and Length of Exposure (p < 0.00001). Orange juice resulted in greater mineral loss of enamel after 28 days. None of the test products was associated with recovery of tooth enamel microhardness.